Health personnel and knee osteoarthritis: April as a reminder of a neglected risk - Vukomanović, Aleksandra (Vojnosanitetski pregled, 2026)
Although often viewed as a condition of the general population, clinical observations indicate that a substantial proportion of knee-pain consultations due to osteoarthritis involve healthcare workers, suggesting a potential burden that exceeds expectations for age-matched adults. Existing research reports a high incidence of knee symptoms among healthcare workers, including a 47% prevalence of work-related knee musculoskeletal disorders in perioperative nurses. However, these studies focus on symptoms rather than diagnosed osteoarthritis, leaving the true burden of structural disease in this population understudied. Occupational demands such as prolonged standing, extensive walking, frequent pivoting, kneeling, squatting, and physically intensive patient handling impose ongoing stress that may accelerate joint degeneration. Increasing retirement age further extends years of exposure, increasing the risk of chronic musculoskeletal conditions. Despite this, knee osteoarthritis remains largely absent from occupational health and safety policies. Low-cost workplace interventions, such as structured movement breaks, brief strength exercises, and consistent access to assistive devices, represent promising approaches, even though current evidence remains limited, and further research is needed to confirm their preventive effect. Legislative measures, such as reduced working hours for older employees, may help mitigate cumulative strain. Emerging technologies, including robot-assisted patient handling, show the potential to reduce high-force exposures. Recognizing knee osteoarthritis as a preventable occupational health issue is essential for protecting the mobility, well-being, and professional longevity of the healthcare workforce.
Keywords: age factors; health personnel; musculoskeletal diseases; occupational exposure; osteoarthritis, knee; risk assessment.